Determination of Electromagnetic Impulse Controlling Drop Formation at Welding with melting Electrode - S. V. Demidkov; V. A. Zankevich; N. D. Bailuk; V. D. Sizov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Regularities on destruction of a conducting non-magnetic jet have been determined within  the limits of magnetic hydrodynamics model when the jet was subjected to longitudinal and azimuthal magnetic fields. The obtained regularities of the process makes it possible to apply them efficiently for controlling parameters of metallurgical processes and metal-transfer process at welding.